HUBUNGAN USIA DAN PARITAS IBU BERSALIN DENGAN KEJADIAN KPD - Yulia Netri (STIKES Keluarga Bunda Jambi, 2019)
The incidence of Early Rupture of Amniotic fluid (KPD) in Indonesia rangers from 4,5% to 7.,6% of all pregnancies, whereas in India it ranges from 6% to 12%. This number is a problem that is still not resolved, especially in developing countries. The incidence of KPD ranges from 3-18% that occurs in preterm pregnancies, whereas at term pregnancies around 8-10%, pregnant women come with the condition of the KPD, where 30-40% are preterm pregnancies at the Regional General Hospital which is the place of reference in Indonesia (Sulistyawati, 2014). The aim of the study was to determine the relationship of age and parity of maternity with the incidence of premature rupture of membranes in Raden Mattaher General Hospital of Jambi Province in 2019. The results showed an association between age with the incidence of premature rupture of membranes in Raden Mattaher Hospital Jambi Province p-value 0,009 and presence the relationship between parity and the incidence of premature rupture of membranes in Raden Mattaher General Hospital, Jambi Province, p-value 0,034. It is expected that the results of this study midwives can improve Antenatal Care services that are more qualified and able to detect risk factors in pregnant women to prevent the risk of occurrence of premature rupture of membranes such as reminding mothers of age and parity the risk of premature rupture of membranes.